Imaging manifestations of cervical aggressive fibromatosis: a case report and literature review - Huang, Zhilan; Li, Jinghong; Xu, Houyun; Liu, Jiaying; Yang, Tian; Zhang, Caijuan; Jin, Xuan; Hu, Jibo; Yang, Jun (Frontiers in Oncology, 2024)
Cervical aggressive fibromatosis is a rare intermediate tumor characterized by invasive growth. Aggressive fibromatosis (AF), also referred to as desmoid-type fibrosarcoma or grade I fibrosarcoma, is a clonal proliferative lesion of fibroblasts located in deep soft tissues. While many cases have been reported, there are relatively few involving aggressive fibromatosis in the anterior inferior margin muscle space of the neck trapezius muscle. We present a case of pathologically confirmed left cervical aggressive fibromatosis, admitted to the Fourth Affiliated Hospital of Zhejiang University. The initial ultrasound and magnetic resonance imaging (MRI) scan of the patient revealed a mass in the left cervical dorsal muscle space, which slowly increased after one year. An enhanced MRI scan initially diagnosed the mass as a left cervical schwannoma. The patient underwent neck soft tissue lesion resection surgery, with postoperative confirmation of cervical aggressive fibromatosis. Our case suggests that fibromatosis cannot be ruled out, and the low-signal cord-like non-enhanced areas, representing collagen fiber characteristics after enhanced scanning, are significant imaging features in diagnosing cervical fibromatosis. Based on the available literature, we have conducted preliminary research on the clinical presentation, imaging manifestations, diagnosis, and differential diagnosis of cervical aggressive fibromatosis to improve clinical understanding and ensure timely clinical treatment.